Modeling Microenvironmental Regulation of Glioblastoma Stem Cells: A Biomaterials Perspective - Heffernan, John M.; Sirianni, Rachael W. (Frontiers in Materials, 2018)
Following diagnosis of a glioblastoma (GBM) brain tumor, surgical resection, chemotherapy, and radiation together yield a median patient survival of only 15 months. Importantly, standard treatments fail to address the dynamic regulation of the brain tumor microenvironment that actively supports tumor progression and treatment resistance. It is becoming increasingly recognized that specialized niches within the tumor microenvironment maintain a population of highly malignant glioblastoma stem-like cells (GSCs). GSCs are resistant to traditional chemotherapy and radiation therapy, suggesting that they may be responsible for the near universal rates of tumor recurrence and associated morbidity in GBM. Thus, disrupting microenvironmental support for GSCs could be critical to developing more effective GBM therapies. Three-dimensional culture models of the tumor microenvironment are powerful tools for identifying key biochemical and biophysical inputs that impact malignant behaviors. Such systems have been used effectively to identify conditions that regulate GSC proliferation, invasion, stem-specific phenotypes, and treatment resistance. Considering the significant role that GSC microenvironments play in regulating this tumorigenic subpopulation, these models may be essential for uncovering mechanisms that limit GSCs malignancy.